Segmental and intonational analysis of Drogheda English - Kalaldeh, Raya Ali (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2011)
This study is concerned with describing the variety of English used in Drogheda, the main town in the North-East of Ireland. The town of Drogheda is approximately 35 miles away from the capital city, Dublin. It also lies within the linguistic boundary zone that separates the two major Irish English varieties: Northern Irish English and Southern Irish English. The study presents a detailed descriptive analysis of the variety’s segmental system including both the vocalic and the consonantal system. A particular emphasis is on the intonational aspects of this variety. Dialectal studies in intonation are increasingly attracting interest and contributing to our understanding of how the intonation system of a language works. In the first part of the study I carry out acoustic and auditory analysis on the speech of local informants from Drogheda to investigate vocalic and consonantal realizations. The findings suggest that Drogheda English has typical Southern segmental features with few Northern traces. In particular, the analysed vowel system shows a robust vowel length distinction between short and long vowels, which is not evident in many Northern Irish English varieties.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin